Mechanisms of dialectical change - Albert Martin (Management Revue, 2009)
Dialectics as a scientific method has its limitations. Dialectics as an intrinsic aspect of reality is an eminent and essential force in social life. Dialectics is about structures and dialectics is about change. This article shows how dialectic mechanisms work. The general considerations are illustrated by cases of organizational, strategic and technological change. We describe some types of dialectical structures and discuss what conditions may be responsible for activating the dialectical mechanism.
Keywords: 650; mechanisms; dialectics; change processes; organizational change; strategic change; technological change